Large‐Area Alignment of Tungsten Oxide Nanowires over Flat and Patterned Substrates for Room‐Temperature Gas Sensing1. Issue 1 (20th November 2014) - Cheng, Wei; Ju, Yanrui; Payamyar, Payam; Primc, Darinka; Rao, Jingyi; Willa, Christoph; Koziej, Dorota; Niederberger, Markus
Abstract Alignment of nanowires over a large area of flat and patterned substrates is a prerequisite to use their collective properties in devices such as gas sensors. In this work, uniform single‐crystalline ultrathin W18O49 nanowires with diameters less than 2 nm and aspect ratios larger than 100 have been synthesized, and, despite their flexibility, assembled into thin films with high orientational order over a macroscopic area by the Langmuir–Blodgett technique. Alignment of the tungsten oxide nanowires was also possible on top of sensor substrates equipped with electrodes. Such sensor devices were found to exhibit outstanding sensitivity to H2 at room temperature.